Exploring the Multimodal Approach in Pre-Service Chemistry Teacher Education: Perspective from Students and Lecturers - Marfuatun Marfuatun; Nahadi Nahadi; Galuh Yuliani; Hernani Hernani (Qubahan Academic Journal)
This study aims to investigate the implementation of a multimodal approach in the learning process and the summative tests of pre-service chemistry teacher education. Data were collected through Google Forms using semi-structured questions. Data were compared with analysis handbooks and summative test documents. The results show that most pre-service chemistry teachers have a multimodal learning style. However, the application of the multimodal approach in chemistry courses has not been extensively implemented due to several challenges. For instance, the time required for preparation can be a significant barrier, as creating and organizing multiple modes of communication can be time-consuming. The complexity of creating media is another challenge, as it requires technical skills and resources. Additionally, the characteristics of students who do not support independent learning can hinder the implementation of a multimodal approach. The most commonly used media in applying the multimodal approach are videos and PowerPoint presentations, supplemented by direct explanations from lecturers. Most of the test techniques used by lecturers were in written form, owing to the difficulties in developing multimodal tests. This study implies an urgent need for the development of multimodal test instruments to accommodate differences in students' learning styles.